The toxicity of phthalocyanines to the aquatic plant Lemna minor (duckweed) - testing of 31 compounds - Jančula, Daniel; Maršálek, Blahoslav (Chemosphere, 2012)
Phthalocyanines are prospective chemicals that have applications in industry, medicine and biology due especially to their architectural flexibility and production of reactive oxygen species. Although they are used in so many areas of human activities nowadays, there is still little knowledge of their ecotoxicity. Here we present the first observation of their toxic effects on representatives of the aquatic plants Lemna minor. The tested phthalocyanines possess a wide spectrum of phytotoxicity ranging from seldom (>50 mg L(-1)) to highly toxic 0.11 mg L(-1). Moreover, the potential of phthalocyanines to be used as selective cyanocides or herbicides is discussed as well.
Keywords: Indoles; herbicidy; indoly; látky znečišťující životní prostředí; Plant Roots; Araceae; kořeny rostlin; Environmental Pollutants; Herbicides